Metode Selective Mining untuk Antisipasi Penurunan Kadar Bijih Nikel dari Data Pemboran terhadap Realisasi Hasil Penambangan pada Blok Yudistira PT Elit Kharisma Utama, Desa Morombo, Kecamatan Lasolo, Kabupaten Konawe Utara, Provinsi Sulawesi Tenggara - Hazqan Hari Asri; Yoszi Mingsi Anaperta (Departemen Teknik Pertambangan FT UNP, 2018)
Abstract. PT. Elit Kharisma Utama (EKU) is the owner of Mining Business License (IUP) engaged in nickel ore mineral commodity, the project location is located in Morombo Village, Lasollo Sub-district, Konawe Utara District, Povinsi Tenggara Tenggara. One of the obstacles in nickel ore mining is the change of nickel ore content (Ni) from drill data that is not in accordance with the level of mining realization results, this mismatch can decrease the quality of production. In mining operations on the front of the Yudhistira block mine, a case of production report data in January 2018 showed that the result of laboratory analysis showed a significant decrease in nickel ore 0.12% content from exploration data on mining content. In this research applied selective mining method on nickel ore excavation activity at mining front. The objective of this research is to know how the change of nickel ore content (Ni) from drill data with the realization of mining and the result of data processing will be analyzed for subsequent can be produced a recommendation. The research method consists of making block model from drill point data and processing of result of mining realization to know the level. The next step is to analyze the level data to know the average of nickel ore content. The average result of mining realization is Ni = 1.80%. while the difference of content from drill data with the realization of mining is Ni = 0.04%. From the research results can be concluded that the content of mining results in accordance with the contract of sale Ni = 1.84% -1.80% reject.Keywords: Nickel, drill hole, Blok Model, Selective Mining, Grade